Sleep apnea and REM sleep behavior disorder in patients with Chiari malformations - Henriques-Filho,Paulo Sérgio A. (2008)
BACKGROUND: Chiari malformations (CM) may result in the appearance of REM sleep behavior disorder (RBD) and sleep apnea syndrome (SAS) that can be considered markers of brain stem dysfunction. PURPOSE: To evaluate the frequency of RBD and SAS in patients with CM type I and II. METHOD: Were evaluated 103 patients with CM by means of full night polysomnography. Were scoring different sleep stages, frequency of abnormal movements (through video monitoring) and abnormal respiratory events. RESULTS: Of the 103 patients, 36 showed CM type I and 67 CM type II. Episodes of RBD were observed in 23 patients. Abnormal apnea-hypopnea index (AHI) was observed in 65 patients. CONCLUSION: The high rate of RBD suggests that this parassomnia and the increased frequency of central sleep apnea episodes, may be considered as a marker of progressive brain stem dysfunction.